Cover Image. Issue 4 (June 2017) - Suzuki, Takao K.
Abstract : On the cover : The cover image, by Takao Suzuki, is based on the Perspective and Hypothesis On the Origin of Complex Adaptive Traits: Progress Since the Darwin Versus Mivart Debate, DOI10.1002/jez.b.22740 .